Breastfeeding and humanitarian emergencies: the experiences of pregnant and lactating women during the earthquake in Abruzzo, Italy - Angela Giusti; Francesca Marchetti; Francesca Zambri; Elide Pro; Eleonora Brillo; Sofia Colaceci (BMC, 2022)
Abstract Background Emergencies have a great impact on infant and young child feeding. Despite the evidence, the recommended feeding practices are often not implemented in the emergency response, undermining infant and maternal health. The aim of this study was to explore the experiences of pregnant and lactating women during the earthquake emergency that occurred in L'Aquila on 6 April 2009. Methods The study design was qualitative descriptive. Data were collected by individual semi-structured interviews, investigating the mother's experiences of pregnancy, childbirth, breastfeeding, infant formula or complementary feeding during the emergency and the post emergency phase. Data analysis was categorical and was performed by using N-Vivo software. Results Six women who were pregnant at the time of the earthquake were interviewed in January 2010. In addition to the essential needs of pregnant and lactating women, such as those related to the emergency shelters conditions, the main findings emerged from this study were: the reconfiguration of relationships and the central role of partners and family support; the need of spaces for sharing experiences and practices with other mothers; the lack of breastfeeding support after the hospital discharge; the inappropriate donations and distribution of Breast Milk Substitutes. Conclusions During and after L'Aquila earthquake, several aspects of infant and young child feeding did not comply with standard practices and recommendations. The response system appeared not always able to address the specific needs of pregnant and lactating women. It is urgent to develop management plans, policies and procedures and provide communication, sensitization, and training on infant and young child feeding at all levels and sectors of the emergency response.